Internal Engagement, Governance Effectiveness, and Traditional Arts Sustainability: A Case Study of the Palembang City Arts Council - Akbariansyah; Muhsin Ilhaq; Syafwatul Putria Hidayatullah; Mediarita Agustina (Journal of Education and Teaching Learning, 2026)
The sustainability of traditional arts is not only determined by artistic preservation efforts but also by the effectiveness of cultural institutions that manage and develop them. This study aims to analyze the dynamics of internal engagement among members of the Palembang City Arts Council (DKP) and its implications for governance effectiveness and the sustainability of traditional arts. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving DKP administrators and members. Data were analyzed using thematic analysis to identify patterns of emotional, cognitive, creative, and organizational engagement. The findings reveal that emotional engagement serves as the foundation for members’ commitment to cultural preservation, which subsequently encourages cognitive engagement in organizational decision-making. Cognitive engagement fosters creative engagement through program innovation and cultural initiatives, while creative engagement strengthens organizational engagement through active participation and collaboration. These interconnected dimensions contribute to governance effectiveness, reflected in improved coordination, communication, and program implementation. Effective governance further supports the sustainability of traditional arts through cultural regeneration, knowledge transfer, and adaptive cultural programs. This study proposes a conceptual model linking internal engagement, governance effectiveness, and traditional arts sustainability, thereby extending engagement theory within the context of cultural governance and arts management.